2014
DOI: 10.18632/oncotarget.2636
|View full text |Cite
|
Sign up to set email alerts
|

FHIT loss-induced DNA damage creates optimal APOBEC substrates: Insights into APOBEC-mediated mutagenesis

Abstract: APOBEC cytidine deaminase activity is a major source of hypermutation in cancer. But previous studies have shown that the TC context signature of these enzymes is not observed in sizable fractions of cancers with overexpression of APOBEC, suggesting that cooperating factors that contribute to this mutagenesis should be identified. The fragile histidine triad protein (Fhit) is a tumor suppressor and DNA caretaker that is deleted or silenced in >50% of cancers. Loss of Fhit protein activity causes replication st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 34 publications
(56 reference statements)
1
56
0
Order By: Relevance
“…Recent studies have identified APOBEC mutation patterns in TP53 in BC (Lindley 2013) and lung adenocarcinoma (Waters et al 2015). Although these studies are useful to better understand the sequence and codon context of mutation formation in TP53, the amount of etiological information they reveal is limited compared with multigene studies using NGS.…”
Section: Mutation Patterns As Signatures Of Mutagenic Processesmentioning
confidence: 99%
“…Recent studies have identified APOBEC mutation patterns in TP53 in BC (Lindley 2013) and lung adenocarcinoma (Waters et al 2015). Although these studies are useful to better understand the sequence and codon context of mutation formation in TP53, the amount of etiological information they reveal is limited compared with multigene studies using NGS.…”
Section: Mutation Patterns As Signatures Of Mutagenic Processesmentioning
confidence: 99%
“…The authors suggest that BIR arising from defects in replication, rather than strand resection during the repair of DSBs, could account for the longer stretches of strand-coordinated editing seen in some kataegis events. Replication stress and A3-induced mutagenesis have recently been linked to loss of a chromosomal fragile site gene, FHIT [63]. FHIT is frequently lost very early in tumor development, causing replication stress due to deoxythymidine triphoshate (dTTP) depletion [64].…”
Section: Availability Of Ssdna Substratementioning
confidence: 99%
“…FHIT is frequently lost very early in tumor development, causing replication stress due to deoxythymidine triphoshate (dTTP) depletion [64]. When genomic sequences from lung adenocarcinomas were stratified by A3B and FHIT expression, those with high A3B and FHIT loss showed significantly higher A3 signature mutation loads than high A3B expressers with normal FHIT levels, thus the mutagenic potential of A3B may be unleashed in the absence of FHIT [63].…”
Section: Availability Of Ssdna Substratementioning
confidence: 99%
“…Replication stress is a hallmark of cell transformation and this stress causes the uncoupling of the polymerase, which facilitates A3 deamination by generating ssDNA targets [200,202,203]. The generation of increased amounts of ssDNA promotes the activity of A3 and increases the mutational frequency Thus, it is notable that A3B is not problematic until a cellular alteration occurs that increases A3B expression and increases replication stress [177,192,203].…”
Section: Role Of Apobec In Somatic Mutagenesismentioning
confidence: 99%
“…The generation of increased amounts of ssDNA promotes the activity of A3 and increases the mutational frequency Thus, it is notable that A3B is not problematic until a cellular alteration occurs that increases A3B expression and increases replication stress [177,192,203]. In contrast, the ssDNA generated on the nontranscribed strand during transcription is accessible at multiple times during the cell cycle of a normal or transformed cell, especially during RNA polymerase stalling [20,21].…”
Section: Role Of Apobec In Somatic Mutagenesismentioning
confidence: 99%